La disgiuntura del tempo: sulla differænza derridiana tra spettro e spirito - Palombi, Fabrizio (Bollettino Filosofico, 2021)
The contribution aims to select some specific parts of Jacques Derrida’s book, entitled Spectres of Marx (1993), in order to propose a preliminary etymological and historical contextualization of the meaning of the term “spectrum”. This overview will devote special attention to the resemantization of the term that was imposed by Isaac Newton. The article will subsequently examine the theoretical difference between “spectre” and “spirit” through the Derridean neographism of différance and the analysis of William Shakespeare’s “out of joint”. The idea is to clarify the disarticulation of the traditional interpretation of time, proposed by Derrida. These argumentation will, in turn, make reference to specific aspects of Derrida’s reading of circumscribed sections of Martin Heidegger’s philosophical reflection and of Sigmund Freud’s psychoanalytic research. Keywords: Freud, Heidegger, Newton, Spectrum, Spirit